The value of bronchoscopy in patients with non‐massive haemoptysis and a clear or benign computer tomogram scan. (26th December 2020) - Murphy, Declan C.; Jackson, Karl; Johnston, Robert; Welsh, Sarah; Webster, Rebecca; Lapsley, Rebecca; Shah, Hussun‐Ara; Mitchell, Daniel; Aujayeb, Avinash
Abstract: Introduction: The preferred diagnostic pathway for patients presenting with non‐massive haemoptysis and normal or benign computer tomography (CT) radiological findings is unclear. The common approach is to investigate with both CT and bronchoscopy, irrespective of patient‐specific factors. The value of performing fibreoptic bronchoscopy (FOB) in patients with non‐massive haemoptysis and clear or benign CT findings remains undetermined. We aimed to investigate its value using a large retrospective case series. Material and Methods: A retrospective review of 4376 FOBs performed in Northumbria Healthcare NHS Foundation Trust from January 2012 to December 2019 for patients presenting with haemoptysis and clear or benign CT findings. Statistical analysis was performed to describe patient‐specific variables, clinical characteristics, pathological findings and subsequent management decisions. Results: A total of 4376 FOBs were performed during the study period, 275 were indicated to investigate non‐massive haemoptysis. Two hundred and fifty‐nine patients underwent a CT scan (158 before and 101 after FOB); 16 never had a CT because the treating physician did not feel it was necessary. About 258 CT scans showed normal anatomy. All patients underwent FOB; 192 showed normal findings. Bronchoscopic findings did not alter clinical management in 274 patients. One patient was referred to the ear, nose and throat department following the identification of polypoid vocal cord lesion which, following thorough investigation, was confirmed as benign. Conclusion: FOB provides minimal value for identifying lung malignancies in patients with non‐massive haemoptysis and a clear or benign CT scan irrespective of patient‐specific risk factors. Cost savings would be associated if physicians altered practice accordingly.